Does cognitive flexibility affect the course of labor? A prospective study. Issue 2 (13th December 2019) - Asali, Aula; Miller, Netanella; Engel, Offra; Haj‐Yahia, Nasreen; Cohen, Omer; Ben‐Kimhy, Reut; Biron‐Shental, Tal
Abstract: Objective: To evaluate cognitive flexibility and labor and delivery outcomes. Methods: A prospective study was conducted of nulliparas with singleton term pregnancy, admitted for labor to a tertiary referral center from 1 January to 31 July, 2017. After epidural anesthesia, parturients completed the validated Psychological Flexibility Questionnaire (20 questions that evaluate a person's level of cognitive flexibility) before delivery. They were asked to grade (from 1 to 10) their hope for vaginal delivery (Hope score). Within 2 hours after delivery, they graded (1–10) the similarity between their delivery and their expectations (Expectation score). Outcomes of the flexible versus less flexible group were compared. Results: Among the flexible (n=120) versus less flexible (n=40) group, vaginal delivery was more common (74.2% vs 20.8%) than vacuum extraction (20.8% vs 35%) or cesarean delivery (5% vs 12.5%) ( P =0.031). High Expectation score and delivery without grade III–IV perineal tear ( P =0.032) were correlated. Groups were similar regarding Expectation ( P =0.163) and Hope scores ( P =0.591). The mode of delivery of parturients was not correlated with their mothers' ( P =0.836) or sisters' ( P =0.758). Conclusion: High cognitive flexibility increases the likelihood of vaginal delivery. These findings support the mind–body correlation. Maternal cognitive perceptions can influence labor and delivery and should be considered when counseling patients during labor. Abstract : High cognitive flexibility affects pregnancy outcomes by increasing the likelihood of vaginal delivery.